Circularly polarized hexagonal ring microstrip patch antenna with asymmetrical feed and DGS. Issue 4 (24th December 2019) - Maurya, Rakesh Kumar; Kanaujia, Binod K.; Gautam, A. K.; Chatterji, S.; Singh, Anil Kumar
Abstract: A novel circularly polarized hexagonal ring microstrip patch antenna with asymmetrical feed is proposed for S, C, and X‐band applications. A semi‐arc‐shaped slot is integrated into the ground plane, and the hexagonal ring is tilted by an angle of 25° with respect to the microstrip‐line feed (asymmetric), which creates a circularly polarized UWB. The simulation of the proposed antenna is carried out using Ansoft HFSS v.13 and the measurement is done with an N5230A vector network analyzer. The simulated and the measured results of our proposed antenna are in good agreement. The successful implementation of the asymmetrical feed shows a broader impedance bandwidth of 134% (B.W = 9.55 GHz) from 2.34 to 11.89 GHz at 7.12 GHz of the center frequency. The 3‐dB axial ratio B.W is 2.8% (7.1‐7.3 GHz) and 21.8% (9.8‐12.2 GHz) in the UWB range. The average gain of the proposed antenna is 4.15 dBi. Good RHCP waves are also found in the x‐z and y‐z planes. The proposed antenna can be effectively used in S, C, and X‐band applications.